Samply.MDR - A Metadata Repository and Its Application in Various Research Networks - Kadioglu, Dennis; Breil, Bernhard; Knell, Christian; Lablans, Martin; Mate, Sebastian; Schlue, Danijela; Serve, Hubert; Storf, Holger; Ückert, Frank; Wagner, Thomas; Weingardt, Paul; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2018)
Collaboration in medical research is becoming common, especially for collecting relevant cases across institutional boundaries. If the data, which is usually very heterogeneously formalized and structured, can be integrated, such a collaboration can facilitate research. An absolute prerequisite for this is an extensive description about the formalization and exact meaning of every data element contained in a dataset. This information is commonly known as metadata. Various research networking projects tackle this challenge with the development of concepts and IT tools. The Samply Metadata Repository (Samply.MDR) is a solution for managing and publishing such metadata in a standardized and reusable way. In this article we present the structure and features of the Samply.MDR as well as its flexible usability by giving an overview about its application in various projects.
EVALuna2:209468